Hans-Michael Geiger- Informational Efficiency in Speculative Markets- A Theoretical Investigation Informational Efficiency in Speculative Markets (Allokation im marktwirtschaftlichen System, 2018)
The purpose of this work is to provide a critical presentation and some extensions of two perspectives of informational efficiency: On the one hand the neoclassical perspective or «arithmomorphic approach» explains efficiency in terms of a concept mainly based on an explicit economic theory. On the other hand, in the Austrian perspective or «causal genetic approach» attention is drawn to the entrepreneurial element of human decision making related to an arbitrage theory of profit which is not traced back to anonymous market forces but rather to incessant discovery of information guided by entrepreneurial alertness.